نظرية الرواسب وتطبيقاتها - بكاكرة, علي; بكري, زكريا; مراد, عبد القادر (university of eloued جامعة الوادي, 2015)
نستخمص في الأخير أنو بعدما كنا لا نعرف عن معظم السلاسل العددية إلا فكرة عن تباعدىا أو تقاربيا، أوصبحنا بفضل إحدى خبايا التحميل العقدي ونعني بذلك نظرية الرواسب. لحساب ا رسب تابع عقدي، نستطيع ‘يجاد قيمة دقيقة ليذه المجاميع، وذلك بعدة طرق من بينيا الأربعة السالفة الذكر، حيث لا تقل إحداىما شأنا عن الأخرى. وقد حاولنا في ىذه المذكرة المتواضعة توضيح كيفية العمل بيذه الطرق مستعينين ببعض النظريات والتعاريف والخواص المتعمقة باختيار السبل المناسبة وغيرىا، ولفيم القارئ اعتمدنا أمثمة متنوعة ومفصمة الحل. وفي الختام نسأل العمي القدير أن يجعل عممنا ىذا في مي ا زن الحسنات متمنين أن تكونوا قد استفدتم ولو بالقميل لأن أخذ القميل خير من ترك الكثير.We conclude that after the last we do not know about most of the numerical chains only an idea of the divergence or convergence, and we have become, thanks to one of the mysteries of the nodal analysis and we mean sediment theory. To calculate the deposit continued my contract, we can 'Ejad accurate value for these groups, and in several ways, including the four mentioned above, where at least one other affair. And has tried in this modest note to clarify how to work in these ways the aid of some of the theories and definitions and properties related to the selection of appropriate ways and others, and we adopted the reader to understand the variety and detailed examples of the solution. In conclusion, we ask the Almighty to make our work in this balance of good deeds, wishing you had benefited and if taking a little because little is better than leaving a lot.
مذكرة ليسانس رياضيات